HOW RURAL INSTRUCTOR IMPLEMENTS ENGLISH FOR SPECIFIC PURPOSES (ESP): INSTRUCTORâ€™S PERCEPTION - Faturrachman, Yani; Sulaiman, Dady (University of Muhammadiyah Malang, 2020)
Teaching ESP is necessary to be designed by the ESP instructors because one of the teaching ESP requirements is the instructors must prepare the suitable precision of English materials for the ESP students. Hyland (2008:113) states that â€œdesigning lesson plan is one of the performing abilities to describe the instructorsâ€™ beliefs, interest, and values of the studentsâ€™ needs about teaching, language, and languageâ€. From several chronological descriptions, the researcher conveys that he applies the qualitative study as his approach to the study. As follows; (1) semi-structured interview, (2) nonparticipant observation, and (3) documentation. Indeed, the three techniques mostly are usually used by the researcher in order to cover the completely problematical statements in this study. The data were gathered by employing semi structured interview which were like the ESP instructorsâ€™ perception, opinion, and assumption. The result of data indicated that there were several the fact assumptions that the ESP instructors were mostly always implementing the suitable lesson for teaching which were; (1) doing the needs analysis, (2) setting the instructional goals, (3) selecting the materials, (4) selecting the teaching techniques, (5) preparing the teaching media, (6) doing the teaching activities, and (7) adapting the learning sources. Furthermore, the semi structured interview showed that the ESP instructors have described the chronological problems and solutions when they have designed and implemented lesson plan such as; The problems in selecting the properly real ESP material, in order to solve that the ESP instructors proposed the phenomenal perception that they mostly used the communicative language teaching to encounter the fact problems. Finally, the purpose of this study is to develop the way ESP instructors can evaluate their teaching application and learning process so that they can change their perception in implementing a teaching plan. Â Â